Parent-adolescence communication, sex knowledge, and attitude towards premarital sex of female adolescents - Embon, Gina Tercena
The study sought to examine the degree of parent-adolescence communication, levels of sex knowledge, and attitude towards premarital sex of female adolescents. Sixty (60) female fourth year students of Miagao National High School served as participants of the study. Majority of them were in the middle adolescents' ages 15-16 and currently staying with their parents., Design of the study was descriptive. The modified Parent-Adolescence communication Scale , Sex Knowledge Scale, and attitude towards Premarital Sex Scale were utilized for data gathering. Responses were analyzed by getting the frequency and mean of the scores. Results showed that generally 4th year female students of Miagao National High School have good communication with their parents. However the participants tended to have a more open communication with their mother compared with their father. On the level of sex knowledge, participants scored fairly above the mean average. It further revealed that sexual knowledge of the participants was higher on the topics related to productive anatomy but lower on sensitive topics such a contraception and pregnancy. Lastly the study affirms previous studies concluding the adolescents have generally negative attitude towards premarital sex.